A COMBINED FUZZY MULTI-CRITERIA GROUP DECISION MAKING FRAMEWORK FOR MATERIAL SELECTION PROCEDURE: INTEGRATION OF FUZZY QFD WITH FUZZY TOPSIS - Dursun, Mehtap; Arslan, Özlem (International Journal of Industrial Engineering: Theory, Applications and Practice, 2021)
Today, organizations give more priority to new product development (NPD) processes in order to gain competitive advantages and to satisfy customers’ requirements. Identification of a suitable material is a key issue in the design and development of new products. Material selection can be viewed as a complex multi-criteria decision making (MCDM) problem that needs to consider multiple conflicting criteria. The aim of this paper is to develop a fuzzy multi-criteria group decision making methodology, which combines 2-tuple fuzzy linguistic representation model, linguistic hierarchies, quality function deployment (QFD), and fuzzy TOPSIS method to specify the importance of selection attributes in material selection procedure and to determine the most appropriate material alternative that best fits the customers’ requirements. The developed approach is illustrated through a case study of washing liquid material selection procedure.